Об одном свойстве кольцевых Q-гомеоморфизмов относительно p-модуля - Салимов, Р.Р. (Український математичний журнал, 2013)
Знайдено достатню умову скінченної ліпшицевості кільцевих Q-гомєоморфізмів в Rⁿ , n ≥ 2, відносно p-модуля при n − 1 < p < n. Наведено приклад кільцевого Q-гомеоморфізму відносно p-модуля у фіксованій точці, що не є скінченно ліпшицевим. We establish sufficient conditions for a ring Q-homeomorphisms in Rⁿ, n ≥ 2, with respect to a p-module with n − 1 < p < n to have the finite Lipschitz property. We also construct an example of the ring Q-homeomorphism with respect to a p-module at a fixed point which does not have the finite Lipschitz property.